Integrity and Confidentiality of Data Protection on Consumers’ Privacy in Tanzania: A Case Study of TCRA (International Journal of Scientific Research and Management (IJSRM), 2023)
In a world struck by advanced technology in all information and communication parameters, confidentiality and data protection of consumers are vital. However, organisations in diverse business aspects find it challenging to protect consumers’ privacy; hence consumers’ confidence in business declines. This study focuses on the integrity and confidentiality of data protection on consumers’ privacy in Tanzania using TCRA as a case study. The study employed a qualitative approach and a case study design. The researcher preferred purposive sampling, and primary data were collected from 10 respondents who were interviewed. In addition, the study collected qualitative data that were analysed through content analysis. The results of this study revealed that trustworthiness, honesty and responsiveness play a significant role in the integrity and confidentiality of data protection that consequently influences consumers’ privacy. Therefore, the study recommends that the government formulate and implement the personal data protection Act. Also, the study recommends reviewing the regulations to include emerging issues in technology like the Internet of Things (IoT), blockchain, big data and social networks.